M-LoCUS: A Scalable Intervention Enhances Growth Mindset and Internal Locus of Control in Undergraduate Students in STEM - Dhiraj Nallapothula (American Society for Microbiology, 2020)
Student self-beliefs regarding intelligence and ability have been shown to correspond to achievement and persistence in an academic domain. Specifically, previous research has suggested that a growth mindset—or the belief that intelligence is malleable and can increase with effort—is associated with student success. Locus of control is a related but distinct self-belief regarding personal agency over various academic and nonacademic outcomes and has also been associated with study skills and academic persistence. However, academic interventions targeting student mindsets and loci of control have remained relatively underexplored, specifically in the context of undergraduate STEM education. Here, we describe the development and assessment of an intervention encouraging students to adopt a growth mindset and internal locus of control. This five-part intervention is administered entirely online and is therefore independent of individual instructor variability. We administered the intervention in five introductory biology courses and show that the intervention was successful in impacting student mindsets and loci of control across various demographics.